Primary epithelioid sarcoma of the oral cavity: Review of literature and presentation of a rare entity. (10th November 2021) - Brar, Branden R.; Dang, Rushil R.; Noonan, Vikki L.; Salama, Andrew R.
Abstract: Background: Epithelioid sarcoma (ES) is a rare malignancy when diagnosed within the oral cavity. Currently, only four cases of primary ES of the oral cavity have been reported in the literature. The diagnosis of ES is difficult and requires differentiation from other sarcomas, benign inflammatory processes and squamous cell carcinoma. Methods: Herein, we have described a primary ES of the lateral oral tongue in a young female. This is the third case of primary ES of the tongue to be reported. Results: A young female underwent partial glossectomy and post‐operative radiation for definitive treatment of a primary ES of the lateral oral tongue with no recurrence at 18 months. Conclusion: Epithelioid sarcoma is a clinically aggressive sarcoma with poor overall survival. Treatment is primarily based on evidence from limited case reports and treatment of non‐head and neck soft tissue sarcomas. Treatment requires a multimodal approach including surgical excision and often postoperative radiation therapy, and close follow‐up.